Left Atrial Pseudotumor Caused By Caseous Calcification of the Mitral Annulus, Case Report with Review of Literature - Gill, MD, Simpal; Chen, MD, PhD, Frank (North American Journal of Medicine and Science, 2011)
Caseous calcification of the mitral annulus (CCMA) is a rare form of periannular calcification, occurring in 0.06% of all echocardiographic studies and in 0.63% of all patients with mitral annular calcification. Here, we report a case of CCMA manifesting as a left atrial mass. The patient is a 78-year-old African American female with multiple co-morbidities, who presented with symptomatic coronary artery disease and chest pain. A pre-operative echocardiogram revealed a mass in the posterior wall of the left atrium, which did not appear to affect the mitral valve or protrude into the left atrial chamber. Intra-operatively, white toothpaste-like material was removed from the mass lesion. Gross examination revealed multiple fragments of grey-white friable caseous material, measuring 3 x 2.5 x 1 cm in aggregate. Bacterial and fungal cultures from this material were both negative. Microscopic examination showed this material to be amorphous, non-viable, basophilic, and acellular, with foci of calcification. These morphological features were diagnostic for CCMA. Review of the literature indicated that CCMA is a very rare benign lesion, presenting as a round, tumor-like mass with central echolucencies on echocardiography. We believe our case report will further raise the awareness of CCMA so that pathologists and radiologists can get familiar with this rare disease to avoid potential misdiagnosis.